A study on premenstrual syndrome among adolescent girl students in an urban area of West Bengal - Mandal, Ranjana; Sarkar, Aditya Prasad; Ghorai, Supriti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Previous studies in India reported a prevalence of premenstrual syndrome to be 20% in a general population and severe symptoms in 8%. The present study was conducted to study the socio-demographic characteristics of adolescent school girls, to estimate the proportion of premenstrual syndrome among them and to find out factors associated with premenstrual syndrome, if any. Methods: It was a cross-sectional descriptive study conducted at a Kolkata city. Data were collected from the students of Class IX to XII in the classroom using pre-tested pre-designed self-administered questionnaire. Total 278 students were included in the study. Data analysis was done with the help of SPSS version 20.0. Results: The mean age of the students was 15.61 years ± 1.3. 54% of girls reported to have PMS. Out of the affective symptoms in ACOG criteria depression was by 45.7%, anger by 61.2%, irritability by 88.1%, anxiety by 51.8%, confusion by 46.4%, rejection by 24.8, breast pain by 22.7, abdominal distension by 37.5%, headache by 40.6% and swelling of limbs by 5% of girls. Conclusions: Proper medical care and psychological counselling should be sought earlier for increased blood flow during menstruation and dysmenorrhoea to get rid of PMS in adolescent girls.